Teaching Vocabulary by Using Short Stories: A Study at MTs Nashriyah NW Sekunyit - Maulida Maulida; Karyawan Putraidi; Ria Hendriani (Universitas Qamarul Huda Badaruddin, 2026)
Abstract: This study investigates the effectiveness of using short stories as a medium to improve vocabulary acquisition among second-grade students at MTs Nashriyah NW Sekunyit in the academic year 2025/2026. The research employed a quantitative pre-experimental design with one group pre-test and post-test. The sample consisted of 25 students selected purposively. A vocabulary test comprising 25 multiple-choice items was administered before and after treatment. Results revealed a significant improvement in students’ vocabulary mastery, with mean scores increasing from 33.44 in the pre-test to 60.96 in the post-test. The paired sample t-test showed a t-count of -9.752 with a significance value of 0.001 (<0.05), indicating a significant effect of short stories on vocabulary acquisition. These findings suggest that incorporating short stories in language classrooms provides an engaging and effective approach for vocabulary learning.